2001
DOI: 10.1002/jmri.1220
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurement of wall shear stress vectors in bifurcation models and comparison with CFD predictions

Abstract: Steady fluid flow was studied in a simple bifurcation model and in a physiologically realistic model of the human carotid bifurcation. Wall shear stress (WSS) vectors were calculated from phase-contrast (PC) magnetic resonance imaging (MRI) measurements of the velocity field. Velocity measurements in the inflow regions were also used as boundary conditions for computational fluid dynamics (CFD) calculations of WSS, which were compared with those derived from MRI alone. In regions of well-behaved flow, MRI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 14 publications
1
71
0
Order By: Relevance
“…Comparisons of PC-MRA with numerical simulations (CFD) for steady flow have been limited to relatively large vessels (e.g., carotid artery) (11)(12)(13). A good review of combined PC-MRA and CFD is given by Long et al (14).…”
mentioning
confidence: 99%
“…Comparisons of PC-MRA with numerical simulations (CFD) for steady flow have been limited to relatively large vessels (e.g., carotid artery) (11)(12)(13). A good review of combined PC-MRA and CFD is given by Long et al (14).…”
mentioning
confidence: 99%
“…Computer visualization of vascular structure plays a critical role in the diagnosis of vascular diseases, such as stenosis and aneurysm [12][13][14]. Computational fluids dynamics to study blood flow behaviour has to be based on accurate modelling of local vascular geometries [11,12,[14][15][16]. Computer modelling of vascular bifurcation can be achieved in three ways: 1) skeleton based implicit surfaces [17][18][19], 2) blending objects obtained by canal surfaces [20,21], and 3) sweeping disks or spheres along curve [18,22,23].…”
Section: Methods For Modelling Vascular Structuresmentioning
confidence: 99%
“…Previous work [15,16,35] have identified that the vascular WSS has a major effect on the formation of haemodynamic diseases, such as atherosclerotic lesions and Saccular aneurysms although an exact relationship is still uncertain. The maximum curvature of the junction is the most important factor that influences WSS.…”
Section: Design Of Bifurcation Junctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang and Majumdar [6] have investigated asymmetric arterial blood flow with a numerical solution in three dimensions, Ikbal [7] have worked on unsteady response of non-Newtonian in magnetic field without considering periodic body acceleration effect. Kohler et al [8] have investigated the wall shear stress with the help of magnetic resonance imaging by measuring the velocity field and comparing it with simulation outputs. Stroud et al [9] have studied a 2D plaque model using modeling and simulation while Fischer et al [10] worked on numerical method for the computational study of arterial blood flow with turbulence.…”
mentioning
confidence: 99%